Syntaxonomy of Island’s Vegetation of the Azovo- Syvaskyy National Nature Park. Classes: Festuco-Brometea, Agropyretea repentis, Chenopodietea і Artemisietea vulgaris (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Results of syntaxonomical investigations of desert steppes vegetation of the Azovo- Syvaskyy National Nature Park are represented. Park’s vegetation consists of eleven associations that belong to four classes: Festuco-Brometea, Agropyretea repentis, Chenopodietea і Artemisietea vulgaris. Within the class Festuco-Brometea specific character of steppe phytocoenoses of the Central Syvash compared with steppe and forest- steppe zones are found. This specifity is assigned to lesser coenotaxonomical diversity, increase of coenotic role of euxerophyte floristic component and to halophyte group participation. Some conservational issues are discussed.
Keywords: desert steppes, vegetation, syntaxonomy, Festuco-Brometea, the Azovo-Syvaskyy National Nature Park.